KONTRIBUSI MODEL PEMBELAJARAN PAKEM TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS XI IPA SMA NEGERI 31 JAKARTA - Manurung, Alberth Supriyanto (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2017)
The objective of the research is to determine the contribution learning modelPAKEM with mathematic learning result. The study makes use of survey methodwhich implements regression and contribution technique. The research wasconducted at SMA 31 Jakarta, kecamatan Matraman, Jakarta Timur with n = 36using Cluster Sampling technique.The result of research show there is a positivecontribution learning model PAKEM with mathematic learning result. Based on theresult of research, the students mathematic learning result could be enhanced byincreasing learning model PAKEM, since the result of verification simply be able toprove the learning model PAKEM to be significant determinant factors.Keyword: learning model PAKEM, mathematic learning result and contribution